Evaluation of Oral Stereognostic Ability in Completely Edentulous Patients - Rafiq, Fatima; Ahmad, Salman; Rahim, Shoaib; Khalid, Huda; Mehak, Ayesha; Afzal, Sana (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the mean oral stereognostic ability (OSA) score in fully edentulous patients. Study Design: Cross-sectional Study. Place and Duration of the Study: Department of Prosthodontics, Foundation University College of Dentistry & Hospital, Islamabad, Pakistan, from Sep 2024 to Feb 2025. Methodology: A total of 145 patients aged 45 to 75 participated in the study. Four unfamiliar testing tools of different shapes were used to assess OSA, with patients manipulating them intraorally to select corresponding analogues on a table. Each tool was scored from 0 to 3 based on the time taken to recognize it. The study analyzed the relationship between OSA scores and various clinical and demographic characteristics using statistical modeling. Results: The mean age was 59.28±8.19 years, of which 64(44.14%) were men, 81(55.86%), were women, and 87(60%) had experience with dentures. The mean stereognostic tool scores varied from 1.78±0.9 to 1.98±0.7. There were no significant differences in OSA scores according to gender or denture experience (p>0.05). A statistically significant difference was seen between age of the patient and total stereognostic score (p<0.001). A strong negative correlation was observed between OSA scores and period of edentulism (p<0.001). Conclusion: OSA decreases with age and longer periods of edentulism, underscoring the value of early prosthetic rehabilitation. Gender and previous denture experience did not have a significant impact on OSA scores.